2022
DOI: 10.2298/jsc211201012d
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol and malonic acid as corrosion inhibitors seen through the density functional theory perspective

Abstract: Glycerol (G) is the major co-product of biodiesel in the transesteri-fication process. As the clean energy demand increases, the G production also increases and new ways of re-using it are needed. In the last decade, some experimental studies claimed that G and its derivative, malonic acid (MA), could be used as corrosion inhibitors. Yet, at the present, there is few evidence of it and more studies are needed to confirm that G and MA would have a good performance in metal protection. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…The corrosion inhibition is probably related to the adsorption of glycerol molecules on the metal's surface. The density functional theory calculations indicated that adsorption happened mainly through oxygen atoms [22]. The protective crude glycerol layer became thicker as the concentration of the inhibitor increased.…”
Section: Solution σ (µS) Phmentioning
confidence: 99%
“…The corrosion inhibition is probably related to the adsorption of glycerol molecules on the metal's surface. The density functional theory calculations indicated that adsorption happened mainly through oxygen atoms [22]. The protective crude glycerol layer became thicker as the concentration of the inhibitor increased.…”
Section: Solution σ (µS) Phmentioning
confidence: 99%